XRF analyses from Lake Fazilman, Uzbekistan - Lucas Dugerdil; Guillemette Ménot; Odile Peyron; Dilfuza Egamberdieva; Isabelle Jouffroy-Bapicot; Boris Vannière; Jakhongir Alimov; Elise Luneau; Johanna Lhuillier; Sébastien Joannin (PANGAEA, 2025)
This data table contains the X-Ray Fluorescence results for a 227 cm-long core core from Lake Fazilman (Fazilman kul, 40.550406 N, 66.589361 E; 1637 m a.s.l.), collected in July 2021 with a 50 cm Russian corer. The XRF are expressed in counts per second (cps) and were obtained with a XRF Core Scanner 3 in the EDYTEM laboratory, Chambéry, France. A Rhodium X-ray source and Ultralene film were used, with measurements at 10 kV (light elements) and 30 kV (heavy elements). The samples are retrieved from the Lake Fazilman composit sediment core. The results for the Br, Ca, Fe, K, Mn, P, Pb, Rb, S, Sr, Ti, Zr, Zn, as well as the Incoherent (Inc) and Coherent (Coh) scatter signals are provided. The first (PC1) and second (PC2) components of the Principal Component Analysis performed on the XRF data are also provided. The sample depth is given in centimeters and the age in year calibrated BP (age-depth model performed with BACON and the IntCal20 calibration curve based on 15 radiocarbon dating; Blaauw et al., 2011; Reimer et al., 2020).
In: Dugerdil, L et al. (2025): Holocene multi-proxy analyses from Lake Fazilman, Uzbekistan: pollen, NPPs, GDGTs, XRF, magnetic susceptibility, climate and vegetation quantitative reconstructions [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.987394 (DOI registration in progress)